The political economy of Germany under Chancellors Kohl and Schröder : decline of the German model? - Leaman, Jeremy, 1947- (Monographs in German history ;, 2009)
While unification has undoubtedly had major effects on Germany's political economy, the pattern of current policy-making preferences was established at an earlier stage, in particular, at the beginning of the "Kohl-era" in 1982. This essentially neo-liberal pattern can be seen to have dominated the modalities chosen to guide Germany through the process of unification and was mirrored in developments in other OECD countries and in particular within the EU. This book demonstrates that the three policy imperatives (neo-liberal structural reform, European monetary integration, and unification) pro